Práticas parentais de máes adultas e adolescentes com bebês de um a doze meses - Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Altafim, Elisa Rachel Pisani [UNESP]; Schiavo, Rafaela de Almeida [UNESP] (Universidade Luterana do Brasil, 2011)
Parental practices have a primordial role in the children development and is closely related to with behavioral repertoires. The study aimed at examining of mothers, both adult and adolescent ones considering also their babies'age. It identified the parental practices of 111 mothers of babies between one and twelve months, of whom 59 were adults and 52 adolescents. They participated in the study answering an inventory of parental practices. When the age of the babies was taken into consideration, some practices showed significant differences, but when adult mothers' practices were compared to those of the adolescent ones differences were not significant. Results show the importance of understanding the nature of these mothers of babies' practices, as foundation for the development of interventionist programs.

As práticas parentais possuem uma função primordial no desenvolvimento infantil e uma estreita relação com os seus repertórios comportamentais. O presente estudo objetivou analisar práticas de mães de bebês adultas e adolescentes, comparando-as com a idade dos bebês. Participaram 111 mães de bebês de um a doze meses de idade, sendo 59 adultas e 52 adolescentes. As participantes responderam a um inventário de estilos e práticas parentais. Considerando a idade dos bebês, foram encontradas diferenças significativas em relação a algumas práticas. Ao comparar as mães, adultas e adolescentes, não foram encontradas diferenças significativas. Este trabalho mostra a importância de se conhecerem as práticas parentais de mães de bebês, para fornecer subsídios na elaboração de programas de intervenções.
Parental practices of adults and adolescents mothers with babies between one and twelve months
Keywords: Maternal behavior; Parental practices; Adolescent mother; Comportamento materno; Práticas parentais; Mães adolescentes